Kesalahan Berbahasa Dalam Lagu “Tegar” Rossa: Dampaknya Terhadap Makna Dan Penyampaian Pesan - Ulfa Fatimah; Nabila Amanda Pulungan; Erbina Br Sembiring (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Songs are an integral part of human life and play an important role in conveying messages and emotions. However, there are often language errors in song lyrics that go unnoticed. This article discusses language errors in the song "Tegar" sung by Rossa, focusing on the use of the word "tegar". According to the Big Indonesian Dictionary (KBBI), the word "tegar" means "stubborn" or "ngeyel," which has a negative connotation. However, in the song, "tegar" is used to describe fortitude and strength, which is different from its original meaning. This qualitative research aims to understand how language choices in songs affect meaning and message delivery as well as listener interpretation. The results of the analysis show that the use of the word "tegar" in songs can change listeners' perceptions and demonstrate the flexibility of language. Language errors in the context of art are acceptable and even enrich the language with new nuances. This article underlines the importance of paying attention to lyrics in creating quality songs with strong messages.